(untitled) (Research, Society and Development, 2023)
Nursing is a profession that defends help committed to health and is enhanced by technical skills aimed at the well-being of those who receive care, which means ethics and respect for their patients. Postmortem care is the last stage of care for the individual, and the nurse is fully responsible for providing this service. The objective of this study is to know the importance of nursing care in preparing the body after death. This is a bibliographical, qualitative and exploratory review. Data collection took place in the BDENF, SciELo and LILACS databases over the last 10 years, using the DECS: Attitude to Death, Nursing Care, Nursing and Death, including original studies analyzed using the Bardin technique. The results showed that many professionals, when caring for the postmortem body, act mechanized, performing the preparation in a technical way, forgetting the humanization when dealing with the lifeless individual and the bereaved family. In this sense, the care provided by the nursing team in the body after death is fundamental, since it is intrinsically linked to a relationship based on ethics and respect for the individual who is dying, such as bereaved family members, and must demonstrate empathy and humanization. It becomes evident the need for continuing education to instruct these professionals to deal correctly, given the feelings of pain and suffering at this time. It is concluded that the nursing team plays a fundamental role in the process of caring for the body after death, since these professionals are closely linked to both the bereaved family and the dying body itself. It is then up to these professionals to show empathy to the family members, while performing a work based on ethics and professional humanization.